EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) DAN LEARNING CYCLE 5E (LC 5E) DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI TIPE KEPRIBADIAN SISWA - Mahmudati, Rina; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to investigate the effect of the learning models on learning achievement viewed from the personality type of the students. The learning models compared were the cooperative learning model of the TPS, LC 5E, and the classical learning model with scientific approach. The type of the research was a quasi-experimental research. The instruments used were mathematics achievement test on the topic of function and questionnaire of personality type. The data was analyzed by using two way analysis of variance with unbalanced cells. The conclusions of the research were as follows. (1) The mathematic learning achievement of students treated with TPS learning model was as good as that of those treated with LC 5E model, and that of those treated with TPS learning model was as good as that of those treated with classical learning model with scientific approach, and that of those treated with LC 5E model was better than that of those treated with classical learning model with scientific approach; (2) The mathematic learning achievement of students with sanguine personality was better than that of those with melancholic one but was as good as that of those with choleric and phlegmatic personalities, that of those with choleric personality was better than that of those with melancholic one, and that of those with melancholic personality was as good as that of those with phlegmatic, and that of those with choleric personality was as good as that of those with phlegmatic one; (3) In each type of student personality, it could be found that the students treated with Think-Pair-Share had equally good learning achievement to those treated with LC 5E model, the students treated with TPS had equally good learning achievement to those treated with classical learning model with scientific approach, those treated with LC 5E model had better learning achievement than those treated with classical learning model with scientific approach; and (4) In each type of learning models, it could be found that the learning achievement of students with sanguine personality was better than that of those with melancholic one but was as good as that of those with choleric and phlegmatic personalities, that of those with choleric personality was better than that of those with melancholic one, and that of those with melancholic personality was as good as that of those with phlegmatic, and that of those with choleric personality was as good as that of those with phlegmatic one.Keywords: Learning Cycle 5E, Think-Pair-Share, Classical with scientific approach, personality type